The Legitimacy of Privatization: Examination of Changes in Attitudes towards Government Ownership of Business in Ten Countries. (1st November 2020) - Stanisevski, Dragan; French, P. Edward
Abstract : While privatization garners support in the elite international institutions, it is less clear how strongly the public supports it. By conducting a statistical analysis of changes in attitudes towards government ownership of business, based on World Values Survey data from ten countries over 25 years, the authors find that the public support for privatization was not widespread in these countries even in the early 1990s and it steadily declined since then, particularly in Latin America and in South Africa. The study concludes that public administration scholarship should incorporate these findings in order to reexamine its conceptual approaches towards privatization.